Sejarah Pendidikan Islam pada Masa Nabi Muhammmad Saw: Sejarah Pendidikan Islam - Mardinal Tarigan; Sutri Ayu Ramadhani; Fadhilah Paramitha (Jurnal Dirosah Islamiyah, 2024)
The journal discusses the history of Islamic education during the classical era, particularly during the time of Prophet Muhammad and the early generations of Islam. The main focus is to understand the Islamic education system established and implemented by Prophet Muhammad, and how this tradition continued throughout Islamic history. The research method used is literature review, collecting data from various literary sources and documents related to Islamic education. The discussion results show that Islamic education has a universal scope, focusing on the development of moral, spiritual, social, and intellectual aspects of individuals, and has values relevant for application in daily life. The journal also highlights the exemplary role of Prophet Muhammad in character education, as well as the challenges and adaptations of Islamic education methods in facing the developments of the times.